Effect of Injecting Drug User on the Risk of Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome: A Meta-Analysis - Lusiana Dewi Saputri; Vitri Widiyaningsih; Hanung Prasetya (Journal of Epidemiology and Public Health, 2023)
Background: The problem of narcotics abuse is drug users through injecting needles. Injecting drug users are any person who uses narcotics, psychotropics and addictive substances by injection. In addition, another understanding states that injecting drug users (IDU) or Injection Drug Users (IDUs) are users of narcotics/drugs with injecting media. Injecting drug use (IDU) is one of the main causes of HIV infection due to sharing of contaminated injection equipment.Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population = adolescents and adults. Intervention= IDU/Injection Drug User. Comparison= Not an IDU/Injection Drug User. Outcome= HIV/AIDS events. The articles used in this study were obtained from several databases including PubMed, Google Scholar and Scopus. These articles were collected over 3 months. The keywords to search for articles are as follows “IDU (Injection Drug User)” AND “life style“ ”HIV/ AIDS ”. There were 15 studies, 9 cross-sectional and 6 cohort studies published in 2012-2022 that met the inclusion criteria. Analysis was performed with Revman 5.3.Results: 15 articles with a study design of 9 cross-sectional and 6 cohort studies from Canada, China, Ukraine, Virginia, Nepal, Cambodia, Scotland, Boston and Africa. Studies show that IDUs (Injecting Drug Users) have a 2.17 times risk of developing HIV/AIDS compared to non-IDUs for HIV/AIDS, and these results are statistically significant (aOR= 2.71; 95% CI= 1.22 to 6.02; p= 0.010).Conclusion: IDU (Injection Drug User) increases the incidence of HIV (Human Immunodeficiency Virus) / AIDS (Acquired Immunodeficiency Syndrome). Keywords: IDU, lifestyle, HIV/AIDS, Drugs, Meta-Analysis Correspondence:Lusiana Dewi Saputri. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: dewislusiana16@gmail.com. Mobile: +6282328370049.